2019
DOI: 10.1128/aac.01479-19
|View full text |Cite
|
Sign up to set email alerts
|

High In Vitro Susceptibility to the First-in-Class Spiropyrimidinetrione Zoliflodacin among Consecutive Clinical Neisseria gonorrhoeae Isolates from Thailand and South Africa

Abstract: We evaluated the in vitro susceptibility to the first-in-class spiropyrimidinetrione zoliflodacin among recent consecutive clinical Neisseria gonorrhoeae isolates cultured in Thailand (n = 99) (in 2018) and South Africa (n = 100) (in 2015 to 2017). Zoliflodacin was highly active in vitro against all tested isolates (MIC range, 0.004 to 0.25 μg/ml; MIC50, 0.064 μg/ml; MIC90, 0.125 μg/ml), with no cross-resistance to any of the seven comparator antimicrobials. Our data support the initiation of the global phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…A number of studies have been conducted to define the in vitro activity of zoliflodacin against clinical isolates of N. gonorrheae collected around the world (Table ). These studies were remarkably consistent, with the majority resulting in a zoliflodacin MIC 90 value of 0.125 μg/mL. The highest zoliflodacin MIC result from any of the studies was 0.25 μg/mL.…”
Section: In Vitro Microbiologymentioning
confidence: 96%
“…A number of studies have been conducted to define the in vitro activity of zoliflodacin against clinical isolates of N. gonorrheae collected around the world (Table ). These studies were remarkably consistent, with the majority resulting in a zoliflodacin MIC 90 value of 0.125 μg/mL. The highest zoliflodacin MIC result from any of the studies was 0.25 μg/mL.…”
Section: In Vitro Microbiologymentioning
confidence: 96%
“…Studies have also shown zoliflodacin to be effective in ciprofloxacin-resistant strains [ 90 ]. More generally, no cross-resistance has been demonstrated with any previously developed antimicrobials [ 86 , 88 , 89 , 91 , 92 ], making zoliflodacin ideal for any N. gonorrhoeae strain resistant to any currently used antibiotic. Up to now, no strains have been reported with resistance to zoliflodacin, although resistant mechanisms uncovered through in vitro studies suggest amino acid alterations D429N and K450N/T in the GyrB to play significant roles in increasing MICs [ 93 ].…”
Section: Treatment Of N Gonorrhoeaementioning
confidence: 99%
“…Clinical studies on the efficacy of zoliflodacin have been promising. Beginning with in vitro studies, zoliflodacin exhibited rapid inhibition of growth against N. gonorrhoeae [ 95 ], demonstrating potent in vitro activity against “geographically, temporally, and genetically diverse” strains including those that are resistant to ceftriaxone [ 91 ]. Overall, zoliflodacin demonstrated a lower modal MIC, MIC 50 , and MIC 90 to every previously used antimicrobial except with regard to ceftriaxone, where all values were highly comparable [ 90 92 ].…”
Section: Treatment Of N Gonorrhoeaementioning
confidence: 99%
“…Earlier work on zoliflodacin showed that, in ciprofloxacin-resistant clinical isolates from China, introduction of GyrB D429N led to a decrease in ciprofloxacin susceptibility or had no effect on ciprofloxacin MIC 26 . Other studies have suggested that there is no cross-resistance between ciprofloxacin and zoliflodacin in recently sampled clinical isolates 77,78 , likely due to the finding that GyrB D429N mutations have not been identified in sequences from ~13,000 clinical isolates 79 . In contrast, enzymology suggests that ciprofloxacin has modestly decreased potency for the stability of cleaved complexes with GyrB D429N as compared to GyrB 429D (a CC50, a measure of the potency for stability of cleaved complexes, of 3 +/-0.4 for the mutant vs. 1.9 +/-0.7 for the WT) 75 .…”
Section: Discussionmentioning
confidence: 95%